Behavior and Gill profile of Nile Tilapia (Oreochromis niloticus) Induced by Density stress - Dwinna Aliza (Universitas Syiah Kuala, 2014)
The aim of this research was to observe behavior and gill profile of nile tilaphia (Oreochromis niloticus) induced by density stress. A total of 50 nile tilapia fish with the age of 3-8 months and 80-100 bwwere divided into 4 groups. Group I was control group contained 5 fish, group II,III, and IV contained 10, 15, and 20 fish, respectively. Treatment was performed for 24 hours, and fish behavior was observed every 3 hours. Gillsample was examined by anatomical pathology then tissue samples were collected and fixed in 10% Davidson solution, routinely processed,embedded in paraffin, sectioned at 5 microns, stained with hematoxylin and eosin (HE), and examined by light microscopy. The data wasanalyzed descriptively. Behavior changessuch as swim up to water surface and rapid movement of operculum occur earlier than passivemovement and decreased reflex of fish on group II, III, and IV. The anatomical pathology of nile tilapia gills observed were darker colour ofgills, gill rott, and over mucus.Histopathological result showed that haematoma, necrosis, hyperplasia of primary and secondary lamella, andfusion lamella were observed in gills of nile tilapia induced by density stress.____________________________________________________________________________________________________________________Key words: histopathology, nile tilapia, gill, density stress